Understanding the Particularities of an Unconditional Prenatal Cash Benefit for Low-Income Women: A Case Study Approach. (August 2019) - Struthers, Ashley; Metge, Colleen; Charette, Catherine; Enns, Jennifer E.; Nickel, Nathan C.; Chateau, Dan; Chartier, Mariette; Burland, Elaine; Katz, Alan; Brownell, Marni
We explored the particularities of the Healthy Baby Prenatal Benefit (HBPB), an unconditional cash transfer program for low-income pregnant women in Manitoba, Canada, which aims to connect recipients with prenatal care and community support programs, and help them access healthy foods during pregnancy. While previous studies have shown associations between HBPB and improved birth outcomes, here we focus on how the intervention contributed to positive outcomes. Using a case study design, we collected data from government and program documents and interviews with policy makers, academics, program staff, and recipients of HBPB. Key informants identified using evidence and aligning with government priorities as key facilitators to the implementation of HBPB. Program recipients described how HBPB helped them improve their nutrition, prepare for baby, and engage in self-care to moderate the effect of stressful life events. This study provides important contextualized evidence to support government decision making on healthy child development policies.